PERAN MODEL CREATIVE PROBLEM SOLVING DALAM MENINGKATKAN BERFIKIR KREATIF SISWA KELAS XI DI SMK AL-MANAR - Nura Nur’aeni; Siti Qomariyah; Deliyanti Dimyati; Arif Saipullah; Fatchi Mohammad Alfi Salim (STKIP Subang, 2026)
This study aims to determine the role of the Creative Problem Solving model in improving students’ creative thinking skills of grade XI at SMK Al-Manar. This learning model emphasizes the process of solving problems creatively through systematic stages that encourage students to be active, think openly, and generate various ideas and solutions to a problem. This research uses a qualitative approach with a descriptive method. Data collection techniques were conducted through observation, interviews, and documentation. The research subjects include the principal, teachers, and grade XI students who are directly involved in the learning process. The results of the study indicate that the implementation of the Creative Problem Solving model is able to improve students’ creative thinking skills. This can be seen from the increased student participation in learning activities, their ability to express ideas, and the diversity of solutions generated during discussions. In addition, students become more confident in expressing their opinions and are more actively involved in the learning process. However, there are still some obstacles, such as limited learning time and uneven student participation. This study is expected to serve as a reference for developing more innovative learning models to enhance students’ creative thinking skills.